Knowledge, Awareness, and Attitude Regarding Dental Chair Light among Dental Practitioners in North Maharashtra Region: A Cross-sectional Survey - Harish Chaitram Jadhav; Vishwakarma K. Prashanth; Snehal Sakharam Patil; Gargi Somvanshi; Vaibhav Shinde; Roshni Prasad (Journal of Primary Care Dentistry and Oral Health)
Introduction: Dental chair light plays an important role in direct and indirect visibility. Various dental chair lights are available in the market, and dentists should be aware of the advantages and disadvantages of those lights. Protecting one’s eyes is extremely important which can be affected by various ways like such as intensity of light and long working hours in light and it may also be a reason for dental ergonomics. Aim and Objective: The aim of the present study was to evaluate the knowledge, awareness, and attitude regarding dental chair light among dental practitioners. Materials and Methods: The present study was a cross-sectional survey conducted among dental practitioners, conducted in North Maharashtra. Ethical clearance was obtained from the institutional ethics committee. A structured questionnaire was formulated with 13 questions in English language. The first part of the questionnaire was demographic data. The second part consisted of 13 multiple-choice close-ended questions. Questions regarding the knowledge of Halogen light and light-emitting diode (LED) dental chair lights were included. Questions about the harmful effects of dental chair light on eyes were included as well as the effect of dental chair light on curing and bond strength of composite. To evaluate the dental practitioner’s attitude toward the use of various lights, questions related to Halogen and LED lights were included. Results: About 71.6% of dental practitioners prefer LED lights in dental chair setups, but 68.3% of practitioners suffer with tired eyes and various eye problems. Conclusion: Dentists are aware of Halogen and LED lights in dental chair setups. Dentists suffer from fatigued eyes and tired and watery eyes after long hours of working in LED lights also there are several other problems such as the production of radiant heat and effect on bond strength related to LED dental chair light.